WR 121 - English Composition - OER (Public) - Jennifer Kepka (Linn-Benton Community College, 2019)
This is an introductory course meant to both expand your knowledge of good essay form and your confidence in your ability to create concise, clear, and cohesive college essays. We’ll look at several different forms of essays and destroy many great pieces of writing in order to learn how the heck we can do that stuff ourselves.